The Use of Canva in Teaching Writing - Dika Rezkyana; Supriyatin Agustini (UM Purwokerto Press, 2022)
This study aims to investigate teacher's and students' perceptions on the use of Canva in teaching writing. The descriptive qualitative method was used in this study. An English teacher and four students from SMPN 2 Kesugihan, Indonesia, participated in this study. The teacher was selected based on the consideration that she had implemented Canva in teaching writing. A semi-structured interview with an interview guide was used as primary data, and the secondary data was from documentation to collect the data. To cross-check the teacher’s data by conducting interviews with the students. The data is analyzed in several steps, including data reduction, display, verification, and conclusion. The study reveals that Canva can improve students’ critical thinking and creativity in writing procedure text. The editable template in Canva helps students generate ideas, writing context, and structure. On the other hand, internet quota and device problems become the students' challenges in using Canva. This study highlights the use of Canva in teaching writing, but this study did not observe students’ writing activities in using this application.